O exame Celpe-Bras: mecanismo de política linguística para o Programa de Estudantes-Convênio de Graduação (PEC-G) - Dionísio, Cynthia Israelly Barbalho (2017)
The Student Program-Undergraduate Convention (PEC-G) is one of the oldest programs of international cooperation in higher education established by the Brazilian Government in partnership with developing countries of Latin America, Africa and Asia. In its core, there is a language policy of teaching Portuguese as a Foreign Language (PFL) for candidates from non-Lusophone countries. These students can attend PFL courses in Brazil in order to prepare themselves for the Certificate of Proficiency in the Portuguese Language for Foreigners (Celpe-Bras), whose certification is part of one of the requirements to gain entry into Higher Education Institutions (HEIs) by the PEC-G. Considering this scenario, we aim at analyzing the extent in which Celpe-Bras acts as a language policy mechanism for those involved in a PFL course directed towards PEC-G students, assigned to a Federal University in the Northeast of Brazil. For this, we investigated the beliefs of the agents regarding the role of the Portuguese language in the world, of the the Celpe-Bras exam, as well as the relations between this exam and the coordination of the course, the teaching and learning of the PFL. We adopted a multidimensional view of language policy (SPOLSKY, 2004, 2009, 2012), language policy mechanisms (SHOHAMY, 2006) and appropriation of the multiple-layered language policy (MENKEN; GARCÍA, 2014). Methodologically, this study consists of a qualitative interpretative research, based on semi-structured interviews. In the analysis of the data we used the contributions of Textual Linguistics and Argumentative Semantics, especially Koch (2000, 2011). From the textual materiality, we drew relations with the beliefs present in the texts-discourses produced by the agents. The conclusions indicated divergent beliefs about the importance of the Portuguese language in the world, ranging from beliefs that strongly deny its importance to those that emphasize it. In the context of the beliefs about Celpe-Bras, we found out unanimity of the agents in understanding it as highly demanding, although with particularities concerning the interpretation of each one on what would be actually evaluated by the exam. Regarding the Celpe-Bras relations with the coordination of the course, we noticed that a critical situation of conflict with the PEC-G students due to the score on the exam provoked a revision of the meaning of what would be to coordinate the course for this group. Concerning the teaching, Celpe-Bras exam directs the planning, choice of contents, methodology and assessment of students' texts, which is considered by teachers as a negative element. In relation to learning, students demonstrated to insert themselves in the communicative practices proposed by the exam, although they also create unforeseen interpretations about the best way of preparing for it. The study seeks to contribute to the discussion of a multidimensional and multi-layered view of linguistic policy, as well as to the expansion of the debate on the language policies of internationalization in general, and specifically the diffusion of the Portuguese language.